2009
DOI: 10.2166/wst.2009.571
|View full text |Cite
|
Sign up to set email alerts
|

Pollutant load removal efficiency of pervious pavements: is clogging an issue?

Abstract: Pervious pavements in car parks and driveways reduce the peak runoff rate and the quantity of runoff discharged into urban drains as well as improve the stormwater quality by trapping the sediments in the infiltrated water. The paper focuses on presenting results from the laboratory tests carried out to evaluate water quality improvements and effects of long-term decrease in infiltration rates with time due to sediments trapping (clogging) within the pavement pores. Clogging was not found to be a major factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…RossRakesh et al 1999;Somes et al 2000;Greenway et al 2002;Marsalek et al 2002;Deletic & Fletcher 2006;Siriwardene et al 2007;Bratieres et al 2008;Singh & Kandasamy 2009), they relate to performance over months and years rather than decades or the life of the asset. Kadurupokune & Jayasuriya (2009) simulated the performance of a pervious pavement over seventeen years and found that the approach is effective in reducing the volume of runoff and peak flows; however, the authors recognised the need to extend laboratory base simulations to field sites.…”
Section: Assessment Methodologymentioning
confidence: 99%
“…RossRakesh et al 1999;Somes et al 2000;Greenway et al 2002;Marsalek et al 2002;Deletic & Fletcher 2006;Siriwardene et al 2007;Bratieres et al 2008;Singh & Kandasamy 2009), they relate to performance over months and years rather than decades or the life of the asset. Kadurupokune & Jayasuriya (2009) simulated the performance of a pervious pavement over seventeen years and found that the approach is effective in reducing the volume of runoff and peak flows; however, the authors recognised the need to extend laboratory base simulations to field sites.…”
Section: Assessment Methodologymentioning
confidence: 99%
“…Runoff from street surfaces generally contains a large volume of contaminants [15]. LID pavements have been identified as being effective in filtering pollutants like suspended solids (SS) and heavy metals by trapping them within the voids of pavement layers as shown in the literature [16][17][18][19]. With the promising filtration capacity of permeable pavement comes a great concern of its susceptibility to clogging [11].…”
Section: Introductionmentioning
confidence: 99%
“…Average removal efficiencies for NH4-N ranged from 86%-88% and Nitrate-Nitrogen (NO3-N) ranged from 48%-65%, respectively [5]. Kadurupokune and Jayasuriya [6] simulated a 17 year period of stormwater quality sampling on a laboratory scaled permeable pavements, using synthetic urban stormwater consisting of mean concentrations of 141 mg/L, 0.24 mg/L, 2.63 mg/L, and 20 mg/L for total suspended solids, total phosphorous, total nitrogen and oil/greases, respectively. The results showed an average removal efficiency of 96%, 95%, 63% and 94% for these parameters [6].…”
Section: Introductionmentioning
confidence: 99%
“…Kadurupokune and Jayasuriya [6] simulated a 17 year period of stormwater quality sampling on a laboratory scaled permeable pavements, using synthetic urban stormwater consisting of mean concentrations of 141 mg/L, 0.24 mg/L, 2.63 mg/L, and 20 mg/L for total suspended solids, total phosphorous, total nitrogen and oil/greases, respectively. The results showed an average removal efficiency of 96%, 95%, 63% and 94% for these parameters [6]. Furthermore, Blecken et al [7] investigated the effects of varying temperatures for nutrient and sediment removal with biofilters.…”
Section: Introductionmentioning
confidence: 99%